Improvement of competitiveness resort enterprises in the region (for example, the ARC) - Pehushyna, Hanna (Skhid, 2013)
Investigated the competitive advantages of Europe's leading resorts, identifies factors that represent the utility value of domestic resorts business, the ways of improving the competitiveness of resorts enterprises in domestic and world market resorts services